Plunging ranula in children: case report and literature review - Veronica Carlini; Valeria Calcaterra; Noemi Pasqua; Marinella Guazzotti; Mario Fusillo; Gloria Pelizzo (MDPI AG, 2016)
Few cases of plunging ranulas (PRs) occur during childhood and the lesions are frequently misdiagnosed. Here, a PR in a child is reported along with a literature review. A seven-year-old female complaining of swelling in the midline neck, left-submandibular region, was evaluated. No oral cavity or major salivary glands abnormalities were detected. On palpation, a soft, painless, and fluid-containing mass was observed. The suspicion PR was performed by ultrasound. The diagnosis was confirmed with a histopathological examination. The lesion was removed with a cervical approach, without recurrence. PR is an uncommon condition in children under 10 years of age. Differential diagnosis depends on clinical examination and ultrasonography. A computed tomography-scan and magnetic resonance imaging can be performed if the diagnosis remains uncertain. In pediatrics, the key to success of the treatment may rely on the radical excision of the cyst and sublingual gland, via an intraoral or submandibular approach.